Sulfur-doping effects on the supercapacitive behavior of porous spherical graphene electrode derived from layered double hydroxide template - Jeon, Woo-Sik; Kim, Chang Hyo; Wee, Jae-Hyung; Kim, Ji Hoon; Kim, Yoong Ahm; Yang, Cheol-Min (ELSEVIER, 2021)
In this study, we successfully synthesized porous S-doped graphene spheres (SGSs) with an S content of 1.1 at% by chemical vapor deposition on a spherical layered double hydroxide (LDH) template using thiophene (C4H4S) as the S-containing carbon source. The doped S atoms were removed from the SGSs by heat treatment under a H2 atmosphere to give desulfurized graphene spheres (De-SGSs) that retained the original pore structure. The effects of the S-doping on the electrochemical behavior of the SGS supercapacitor electrode were investigated by comparing these behaviors with those of the De-SGS electrode. The results revealed that the SGS electrode exhibited electrical conductivity and surface wettability with the electrolyte that were superior to those of the De-SGS electrode. Furthermore, the SGS electrode showed an extremely high capacitance retention of approximately 100% at a current density of 20 mA cm-2 in an electrolyte of 1 M tetraethylammonium tetrafluoroborate in propylene carbonate (TEABF4/PC), while that of the De-SGS electrode under same conditions was approximately 40%. Thus, due to its excellent electrical conductivity, wettability, and the pseudocapacitive contribution of its S-dopants, the SGS electrode demonstrates an electrochemical performance that is superior to that of the De-SGS electrode.
Keywords: CARBON NANOFIBER; NITROGEN; CO; MICROSPHERES; CATALYSTS; GRAPHITE; NETWORKS; DISORDER